Simulation and Analysis of Welding Distortion of T- Joint Using Ansys” - Mohd Asri, Amir Syafiq (2018)
Shielded metal arc welding (SMAW) is one of the most used in the industries. Wide range of dimension and material of the product that wanted to do the welding should include the possible defect that occur when the welding process is done. This project is focusing on finding the relationship between distortion of the plate and thickness of the plate during welding. The scope of this project is on SMAW welding on stainless steel plate that are joined by T- joined. This project also was focusing on evaluating if the ANSYS is the right software to do the simulation and what subsystem to use in ANSYS that are suitable to do this simulation. The project is using three (3) different thickness of plate. 10mm, 20mm and 30mm. The height and length of the plate remain constant, 80mm and 100mm. conclusion of the project is the lower the thickness of the plate, the higher the distortion of the plate.